The localization of abstract expressionist style in Malaysian art - Abdullah, Sarena (IACSIT, 2009)
This paper discusses the early Abstract Expressionist work in Malaysia with regards to how the styles have been localized and adapted into the Malaysia an context. The early association of the artist labeled as Abstract Expressionists during the 1960s culmirulted in a group exhibition called "GRUP" in 1967 and another exhibition entitled "Tb.e Expressionists of the 1960s" in 1974. It has since then been associated with arti~ts such as Syed Ahmad Jamal and Latiff Mohidin. Since the 1970s the style has been well accepted and most imponantly locallize in terms of Its subjects and thematiC upproach inherent to Malaysia's cultural context.